IMPLEMENTASI PASAL 69 AYAT 4 UU NO 45 TAHUN 2009 TERHADAP KAPAL IKAN BERBENDERA ASING YANG TERTANGKAP TANGAN MELAKUKAN ILLEGAL FISHING OLEH DIT POLAIR POLDA SUMUT - Hariyatmoko Hariyatmoko; Alvi Syahrin; Suhaidi Suhaidi; Edi Yunara (Universitas Sumatera Utara, 2019)
ABSTRACT The theft of fish at sea have caused great loss of fishery in the territory of the Republic of Indonesia. Mandate of the Act No. 45-year 2009 article 69 paragraph 4 to carry out the functions of supervision and law enforcement in the field of fisheries in the area of management of fisheries of the Republic of Indonesia. On the basis of the policy of the Directorate of Police (.dit Polair) Waters of North Sumatra doing the sinking ship of a foreign flagged fishing perpetrators of illegal fishing. Based on the research behind latas will be analyzed the implementation of paragraph 4 of article 69 of the Act No. 45-year 2009 against a foreign flagged ship fish which is caught hands doing illegal fishing with the object of research conducted at the .dit Polair Police Of North Sumatra. The research was carried out using the method of normative legal research. Research data using secondary data and supported by primary data. Data collected with the use of the study of the literature and interviews. The data analysis done with the method of qualitative analysis. Protecting the richness of the waters from the level of illegal fishing which can interfere with the conservation of nature, protect the traditional fishing, improve social welfare and State revenue. Policy action to eradicate illegal fishing puts the magnitude of the law court decisions remains the sinking process when compared to foreign vessels caught hands starting with the evidence sufficient. Implementation of the sinking ship of alien fish by North Sumatran Police Polair Recorded in the maintenance of kamtibmas, law enforcement, as well as provide protection, shelter and service to the community. Nevertheless Recorded Polair Poldasu experiencing obstacles in the application of article 69 paragraph 4 of Act No. 45 of the year 2009. It is because after enactment of the Ordinance, there is a constraint that does not support an increase in production and export in terms of quantity and quality. Based on the above research advice researchers that implementation of article 69 of the Act 45 Years 2009 paragraph 4 needs to pay attention to the basic considerations against the background of the enactment of the Government policy in the prevention efforts illegal fishing. Law enforcement agencies to be more active in conducting dissemination to the public of illegal fishing. Law enforcement must do other efforts can support the success in preventing the occurrence of illegal fishing with the increase in HUMAN RESOURCES, improvement of facilities and infrastructure supporting operasioanal, improve security operations on a regular basis and coordinated. Keywords: the sinking of the ship, Illegal Fishing, Recorded Polair of North Sumatra.